The 23rd IEEE International Symposium on Robot and Human Interactive Communication 2014
DOI: 10.1109/roman.2014.6926325
|View full text |Cite
|
Sign up to set email alerts
|

Storytelling with robots: Learning companions for preschool children's language development

Abstract: Abstract-Children's oral language skills in preschool can predict their academic success later in life. As such, increasing children's skills early on could improve their success in middle and high school. To this end, we propose that a robotic learning companion could supplement children's early language education. The robot targets both the social nature of language learning and the adaptation necessary to help individual children. The robot is designed as a social character that interacts with children as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(91 citation statements)
references
References 24 publications
1
88
0
2
Order By: Relevance
“…Empirical evidence demonstrates that learning with and from a physically present, interactive robot can be more effective than learning from classical on-screen media [14,15,20], and that robots can help children to develop in educational settings [10,18,24,27]. However, at the same time, it is found that suboptimal behaviour of the robot can hamper learning [17].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical evidence demonstrates that learning with and from a physically present, interactive robot can be more effective than learning from classical on-screen media [14,15,20], and that robots can help children to develop in educational settings [10,18,24,27]. However, at the same time, it is found that suboptimal behaviour of the robot can hamper learning [17].…”
Section: Related Workmentioning
confidence: 99%
“…in nursery where toy robots teach the alphabet to kids in a very simple way. More generally, findings from a variety of settings seem to suggest that robots can help small children to develop in an educational setting [10,18,24,27].…”
Section: Introductionmentioning
confidence: 99%
“…We acknowledge that social robots have been used for teaching young children in kindergartens and schools [15]. In addition, some research applies social robots in teaching specific contents (e.g., geometry and literacy) [16,17]. Nevertheless, while the robotics kits engage young children in learning through designing, constructing and programming (operating) robots, social robots engage young children in learning different subjects through their social interaction with robots.…”
Section: Introductionmentioning
confidence: 99%
“…For electronic games to gain the potential for positive effect, they should not only have entertainment value, but should be designed to address a specific problem or to teach and enhance a certain skill (Griffiths, 2002). Further, it is important for parents to be involved when their children play these electronic games, such as by giving them feedback and interacting with them, in order for the children to gain positive skills and behavior (Kory & Breazeal, 2014;Yannier et al, 2015), because in most studies that reported positive effects of computer and electronic games, parent or teachers were involved and supervising the children as they played. Thus, we recommend that parents and caregivers become involved and participate with children as the children play electronic games.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also showed an association between physical play and physical self-concept (Babic et al, 2014). For children to gain any skills or benefits from what they are playing, interaction with others (Kory & Breazeal, 2014), especially parent-child interaction (Radesky, Schumacher, & Zuckerman, 2015), and interactive feedback from their parents, teachers, or siblings are required (Yannier, Koedinger, & Hudson, 2015).…”
Section: Introductionmentioning
confidence: 99%